A case of spindle cell dominant histiocytic sarcoma showing a complete remission after first-line chemotherapy with doxorubicin and ifosfamide. (16th November 2020) - Nakamura, Yusuke; Takemasa, Akihiro; Kushima, Yoshitomo; Soda, Sayo; Ikeda, Naoya; Arai, Ryo; Chibana, Kazuyuki; Nakazato, Yoshimasa; Yokose, Tomoyuki; Shimizu, Yasuo; Niho, Seiji
Abstract : Histiocytic sarcoma (HS), an extremely rare malignancy, usually follows a progressive time course, and patients die within two years of diagnosis. At present, there is no consensus for effective chemotherapy. We report the case of a 54-year-old man who presented with low back pain and left hip joint pain. Imaging for the pain revealed multiple lesions in the mediastinum, vertebral bodies, and left ilium. Biopsies of the mediastinal and vertebral lesions yielded a diagnosis of soft tissue sarcoma. He received standard chemotherapy for sarcoma with doxorubicin and ifosfamide, as the initial pathological diagnosis was soft tissue sarcoma. This is called AI therapy and commonly used for soft tissue sarcoma. Palliative radiation therapy to the left iliac lesion was added for pain control. Complete remission (CR) was achieved after two courses of AI therapy. Subsequent immunopathological examination revealed that the tumor was spindle cell dominant HS. CR was maintained for more than three years. To the best of our knowledge, this is the first report that a CR was achieved by AI therapy as first-line treatment for spindle cell dominant HS, combined with focal bone palliative irradiation. AI therapy could be an effective option as chemotherapy for HS.